IS-09 Feline Pelvic Fracture - Monchanok Vijarnsorn (Hemera Zoa, 2018)
Pelvic fractures are traumatic injuries that account for approximately 20-32 % of appendicular fractures in cats (1). Among these feline patients, fractures of the pelvic floor are commonly found (90%), while the incidences of the sacroiliac luxation and the ilial body fractures have been reported as high as 60% and 48.5% (2, 3).  The causes of pelvic fractures usually involve high impact trauma predominantly road traffic accidents. The patients can suffer significant morbidity and mortality if the concurrent soft tissue injuries were not appropriately diagnosed and managed. The initial assessment of the vital organ systems should be performed to identify life-threatening injuries. The concurrent non-orthopedic injuries can occur as high as 59-72% of the cases and it is of important that the injured patients need to be stabilized before primary repair of the pelvic bone (1).